2008
DOI: 10.1111/j.1365-2591.2008.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo evaluation of dye penetration associated with various dentine bonding agents in conjunction with different irrigation solutions used within the pulp chamber

Abstract: The type of irrigant affected the sealing ability of bonding agents inside the pulp chamber and was material specific. Xeno III had less dye penetration with CHX and povidone iodine whilst sodium ascorbate pretreatment after NaOCl reduced dye penetration with both PBNT and Xeno III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…87,91,96,97 da Silva et al 91 found the effect of 2% I2DDS on the µTBS of different adhesive systems to be materialspecific. They found µTBS to be significantly decreased for ethanol-and water-based adhesive systems (Single Bond, Clearfil SE Bond, and Opti-Bond Plus).…”
Section: Effects On Restorative Treatmentmentioning
confidence: 99%
“…87,91,96,97 da Silva et al 91 found the effect of 2% I2DDS on the µTBS of different adhesive systems to be materialspecific. They found µTBS to be significantly decreased for ethanol-and water-based adhesive systems (Single Bond, Clearfil SE Bond, and Opti-Bond Plus).…”
Section: Effects On Restorative Treatmentmentioning
confidence: 99%
“…In these studies, different methods were employed for the measurement of voids/gaps and leakage; invariably, however, the presence of voids/gaps was measured on 2D images. Some of these studies revealed a positive relationship or correlation between the presence of voids/gaps and leakage . One study revealed a general tendency for increased microleakage in root canals with filling defects, but the authors reported that not all teeth with filling defects leaked .…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge of the relationship between leakage and the presence of voids within filling/luting materials or gaps on their interfacial surfaces derives from studies in which endodontic, restorative, and prosthetic materials and techniques were tested. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] In these studies, different methods were employed for the measurement of voids/gaps and leakage; invariably, however, the presence of voids/gaps was measured on 2D images. Some of these studies revealed a positive relationship or correlation between the presence of voids/gaps and leakage.…”
Section: Discussionmentioning
confidence: 99%
“…References with links to Crossref -DOI ant solutions during root canal treatment and their effect on the adhesive system/pulp chamber bond (19,20). Chemical irrigants such as sodium hypochlorite (NaOCl), commonly used in endodontic treatment, can adversely affect the bond strengths of adhesive systems in contact with dentine pulp chamber walls after endodontic treatment (19) when NaOCl was applied previous to the use of a self-etching priming system (Clearfil™ SE Bond, Prompt™ L-Pop™), better results were obtained than when it was used with a total-etching adhesive (Prime & Bond ® NT).…”
Section: E560mentioning
confidence: 99%